Mentoring in the EFL Practicum - Jedličková, Kamila (Univerzita Karlova, Filozofická fakulta, 2020)
Keywords: Teaching practicum, mentors, mentoring, qualitative research, multiple case study Abstract The teaching practicum is an integral part of teacher education and a key role is played by teacher trainers - mentors. The aim of this thesis is to determine their perception of the practicum, evaluation of their own degree of preparedness, and attitude to the tasks which the role of the mentor involves. The theoretical part describes the roles of the mentor, models of mentoring, concrete mentoring tasks, and also mentors' motivation as well as important skills. It further discusses selected issues in the EFL practicum, namely feedback and self-reflection, observations, preparedness of mentors, and the length of the practicum. The empirical part is comprised of the results of qualitative research in the form of a multiple case study. Five case studies have been carried out in total and data have been processed through the process of coding. The paper then goes on to analyse the findings with regard to the theoretical concepts discussed earlier in the study, and outlines potential research and pedagogical implications. The main findings of the study include mentors' high motivation for their roles and friendly attitude to teacher trainees, as well as their lack of specialised education for teacher trainee. Klíčová slova: Pedagogická praxe, fakultní učitelé, mentoring, kvalitativní výzkum, několikanásobná případová studie Abstrakt Pedagogické praxe jsou nedílnou součástí profesní přípravy učitelů a klíčovou roli v nich sehrávají cviční učitelé - mentoři. Tato diplomová práce si klade za cíl zjistit jejich vnímání průběhu praxí, hodnocení vlastního stupně připravenosti a přístup k úkolům, které role cvičného učitele zahrnuje. Teoretická část zpracovává na základě sekundární literatury role mentora, typy mentoringu, konkrétní úlohy mentorů a v neposlední řadě i jejich motivaci. Dále pojednává o vybraných oblastech pedagogických praxí, konkrétně o zpětné vazbě a sebereflexi, násleších, připravenosti mentorů pro jejich roli a délce praxí. Empirická část práce představuje výsledky kvalitativního výzkumu, který má formu několikanásobné případové studie. Celkem bylo provedeno pět případových studií a data byla zpracována pomocí kódování. Hlavní výzkumná zjištění poukazují na vysokou motivaci a přátelský přístup mentorů ke studentům, ale také na to, že mentorům zcela chybí teoretická průprava pro jejich roli ve vzdělávání budoucích učitelů, což ovšem sami nevnímají jako nedostatek. Práce dále konfrontuje výzkumná zjištění s teoretickými koncepty prezentovanými v první části práce a popisuje jejich možné využití v. Department of the English Language and ELT Methodology Ústav anglického jazyka a didaktiky Filozofická fakulta Faculty of Arts